Cadenas de valor, comercio exterior y diversidad biológica - Gómez de Zea, Rosario (2013)
In Peru, the evidence shows the link between emerging markets and national value chains, articulated to the sustainable use of biodiversity. In this sense, the mega biodiversity and therefore the services provided by ecosystems have contributed to respond to the opportunities offered by the international market. In this context, this paper aims to analyze the economic importance of biodiversity, particularly in the development of value chains in different Peruvian regions, which are part of a diversified export supply.